Submacular choroiditis in common variable immunodeficiency associated with a pathogenic mutation in the tumor necrosis factor gene - Michelle Y. Peng; Judy J. Chen; Aisha Ahmed; Emmett T. Cunningham, Jr. (American Journal of Ophthalmology Case Reports, 2020)
Purpose: To report on a case of submacular choroiditis in a patient with common variable immunodeficiency (CVID). Observations: An 80-year-old man was referred with a diagnosis of a central retinal vein occlusion with CME and later developed intraocular inflammation. History was notable for recurrent bacterial infections and myelodysplastic syndrome known to be due to CVID. Ophthalmic examination and multimodal imaging revealed mild intraocular inflammation, retinal vasculitis, submacular choroiditis, and CME. Genetic testing identified a point mutation in TNFRSF13B, a pathogenic variant in the tumor necrosis factor gene known to be associated with CVID, but not with CVID-associated uveitis. Conclusions and importance: The diagnosis of CVID should be considered in patients with uveitis and a history of recurrent bacterial infections. Genetic testing can support the diagnosis.